2022
DOI: 10.1002/aelm.202200326
|View full text |Cite
|
Sign up to set email alerts
|

A Van Der Waals Photo‐Ferroelectric Synapse

Abstract: For hardware artificial intelligence, the central task is to design and develop artificial synapses with needed characteristics. Here, the design and experimental demonstration of a van der Waals (vdW) photo‐ferroelectric synapse are reported. In the photo‐ferroelectric synapse, the synaptic memory is extracted by reading the photocurrent, and written or edited by electrical pulses. The semiconducting vdW organic‐inorganic halide perovskite ((R)‐(–)‐1‐cyclohexylethylammonium)PbI3 (R‐CYHEAPbI3) photo‐ferroelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…18) Recently, to solve this problem, Li et al, demonstrated optically induced polarization switching in BaTiO 3 -based ferroelectric heterostructures utilizing a two-dimensional (2D) narrow-gap transition metal dichalcogenide semiconductor (TMDs) material MoS 2 as a top electrode. 19,20) Comprising ferroelectrics and 2D narrow-gap TMDs materials, such as MoS 2 and MoTe 2 , can broaden the absorption spectrum of the device, increase the conductivity and improve the output photocurrent, thereby raising the efficiency of photovoltaic devices. 21,22) Our work reports ferroelectric properties of Sc 0.2 Al 0.8 N thin film and researches the switchable FePV effect and photo-diode characteristics of two-terminal Sc 0.2 Al 0.8 N devices.…”
mentioning
confidence: 99%
“…18) Recently, to solve this problem, Li et al, demonstrated optically induced polarization switching in BaTiO 3 -based ferroelectric heterostructures utilizing a two-dimensional (2D) narrow-gap transition metal dichalcogenide semiconductor (TMDs) material MoS 2 as a top electrode. 19,20) Comprising ferroelectrics and 2D narrow-gap TMDs materials, such as MoS 2 and MoTe 2 , can broaden the absorption spectrum of the device, increase the conductivity and improve the output photocurrent, thereby raising the efficiency of photovoltaic devices. 21,22) Our work reports ferroelectric properties of Sc 0.2 Al 0.8 N thin film and researches the switchable FePV effect and photo-diode characteristics of two-terminal Sc 0.2 Al 0.8 N devices.…”
mentioning
confidence: 99%